Vanadium-titanium pellet binder, vanadium-titanium pellets and preparation method of vanadium-titanium pellets

By using the use of magnesium titanium pipe adhesives containing magnesium titanium balls in the preparation process of vanadium titanium ball, the problem of high adhesive cost and low magnesium content in existing craftsmanship, and increasing the titanium titanium piercing ore resistance The effect of pressure strength and reducing expansion rate.

CN119351732APending Publication Date: 2025-01-24HEBEI JINXI IRON & STEEL GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411526915.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the existing vanadium titanium pelletized ore preparation process, the adhesive used has problems of high cost and low magnesium content, resulting in poor compressive strength and preparation quality of vanadium titanium pelletized ore.

Method used

A vanadium titanium group binder, which includes 7%-9%boron tail powder, 19%-22%nickel ore, and 70%-74%of Swedish fine powder. The vanadium titanium ball binding agent reduces the proportion of primitive soap soil, and increases the magnesium content by using boron tail powder containing magnesium.

Benefits of technology

Effectively improve the pressure resistance of the vanadium titanium ball group ore, reduce the expansion rate, improve the quality of preparation, and reduce the cost of preparation, and meet the needs of blast furnace smelting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351732A_ABST
    Figure CN119351732A_ABST
Patent Text Reader

Abstract

The invention provides a vanadium-titanium pellet binder, vanadium-titanium pellets and a preparation method of the vanadium-titanium pellets. The vanadium-titanium pellet binder is prepared from, by mass, 7%-9% of boron tail powder, 19%-22% of nickel ore and 70%-74% of Sweden fine powder. Uniformly mixing the boron tail powder, the nickel ore and the Sweden fine powder to form a vanadium-titanium pellet binder; the Sweden fine powder comprises the following components in percentage by mass: 60%-70% of TFe, 2%-3% of Si < 0 >, 0.2%-0.3% of Ca < 0 >, 0.4%-0.5% of Al < 0 >, 0.03%-0.05% of Ti < 0 >, 7%-8% of water and other impurities. According to the vanadium-titanium pellet binder provided by the invention, solid waste products can be fully utilized, the cost of the binder can be reduced, the addition proportion of original bentonite can be reduced when the vanadium-titanium pellet binder acts on the vanadium-titanium pellets, the magnesium content in the vanadium-titanium pellets can be increased, the compressive strength of the vanadium-titanium pellets is further improved, and the service life of the vanadium-titanium pellets is prolonged. And the quality of the vanadium-titanium pellets is effectively improved, and the preparation cost of the vanadium-titanium pellets is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of vanadium-titanium pellet preparation, and more specifically, relates to a vanadium-titanium pellet binder, a vanadium-titanium pellet and a preparation method of the vanadium-titanium pellet. Background Art

[0002] When using an ironmaking furnace to prepare vanadium-titanium pellets, an adhesive is required to complete the preparation process. Existing adhesives use a large amount of bentonite, which not only has the problem of high cost, but also has a high proportion of original bentonite and a low magnesium content, which will seriously affect the compressive strength of the vanadium-titanium pellets. Therefore, when using the existing preparation process to prepare vanadium-titanium pellets, it is difficult to improve the preparation quality of vanadium-titanium pellets. Summary of the invention

[0003] The purpose of the present invention is to provide a vanadium-titanium pellet binder, a vanadium-titanium pellet ore and a method for preparing the vanadium-titanium pellet ore, which can improve the compressive strength of the vanadium-titanium pellet ore, reduce the expansion rate of the vanadium-titanium pellet ore, and facilitate improving the quality of the vanadium-titanium pellet ore.

[0004] To achieve the above object, the technical solution adopted by the present invention is: to provide a vanadium-titanium pellet binder, the components of the vanadium-titanium pellet binder include: 7%-9% of boron tail powder, 19%-22% of nickel ore and 70%-74% of Swedish fine powder by mass percentage; the boron tail powder, nickel ore and Swedish fine powder are evenly mixed to form the vanadium-titanium pellet binder; Among them, the components of Swedish refined powder include: 60%-70% TFe, 2%-3% SiO2, 0.2%-0.3% CaO, 0.4%-0.5% Al2O3, 0.03%-0.05% TiO2, 7%-8% water and other impurities.

[0005] In one possible implementation, the components of the boron tail powder include, by mass percentage, 4%-5% TFe, 18%-22% SiO2, 1.0%-1.3% CaO, 1.4%-1.7% Al2O3, 0.07%-0.1% TiO2, 34%-48% MgO, 35%-42% water and other impurities.

[0006] In some embodiments, the components of the nickel ore include, by mass percentage, 45%-55% TFe, 2.5%-3.5% SiO2, 0.02%-0.05% CaO, 0.2%-0.6% Al2O3, 0.05%-0.05% TiO2, 5%-10% water, and other impurities.

[0007] In one possible implementation, after the boron tail powder, nickel ore and Swedish fine powder are mixed in proportion, the mass percentage of each component is: 54%-57% TFe, 2.0%-2.9% SiO2, 0.15%-0.30% CaO, 1.6%-2.5% MgO, 1.0%-1.8% Al2O3, 0.02%-0.10% TiO2 and other impurities.

[0008] The scheme shown in the embodiment of the present application, compared with the prior art, the vanadium-titanium pellet binder provided in the embodiment of the present application can make full use of solid waste products and reduce the cost of the binder. The above-mentioned vanadium-titanium pellet binder acts on vanadium-titanium pellets to reduce the proportion of original bentonite, so that the original bentonite is reduced by 4-6kg / t compared with the benchmark sample. By using boron tail powder containing magnesium element, the magnesium content in the vanadium-titanium pellet is increased by 0.8%, thereby improving the compressive strength of the vanadium-titanium pellet, reducing the expansion rate of the vanadium-titanium pellet, effectively improving the quality of the vanadium-titanium pellet, reducing the preparation cost of the vanadium-titanium pellet, and meeting the blast furnace smelting needs.

[0009] The present invention also provides a vanadium-titanium pellet, comprising 65%-70% by mass of vanadium-titanium iron powder, 1.5%-2.5% by mass of copper powder, 1.5%-2.5% by mass of dust ash, 1.3-1.5% by mass of bentonite and a vanadium-titanium pellet binder, wherein the mass percentage of the vanadium-titanium pellet binder is 20%-26%. The vanadium-titanium iron powder, copper powder, dust ash, bentonite and the vanadium-titanium pellet binder are roasted to obtain the pellet.

[0010] In a possible implementation, the mass percentage of vanadium-titanium iron powder is 69%, the mass percentage of copper powder is 2%, the mass percentage of dust ash is 2%, the mass percentage of bentonite is 1.4%, and the mass percentage of vanadium-titanium pellet binder is 24%.

[0011] Compared with the prior art, the vanadium-titanium pellets provided in this embodiment can effectively improve the compressive strength of the vanadium-titanium pellets, reduce the expansion rate of the vanadium-titanium pellets, effectively improve the quality of the vanadium-titanium pellets, reduce the preparation cost of the vanadium-titanium pellets, and meet the needs of blast furnace smelting.

[0012] The present invention also provides a process for preparing vanadium-titanium pellets, comprising the following steps: S100: 7.8-8.5% by weight of boron tail powder, 19-22% by weight of nickel ore, and 70-73.2% by weight of Swedish fine powder are mixed to obtain a vanadium-titanium pellet binder; S200: 20%-26% by weight of vanadium-titanium pellet binder, 65%-70% by weight of vanadium-titanium iron powder, 1.5%-2.5% by weight of copper powder, 1.5%-2.5% by weight of dust removal ash and 1.3%-1.5% by weight of bentonite are mixed evenly to form raw balls; S300: drying, preheating, roasting, homogenizing and cooling the green balls in sequence to obtain vanadium-titanium pellets.

[0013] In a possible implementation, in step S300, the drying bed temperature of the preheating step is 500°C-600°C, the material temperature of the green balls is greater than 60°C, and the cold air volume of the cooling step is 35000m 3 / h-37000m 3 / h.

[0014] In a possible implementation, in step S300, the combustion chamber temperature of the roasting process is 1000-1100°C, and the combustion chamber pressure of the roasting process is 13000m 3 / h-15000m 3 / h.

[0015] In a possible implementation, after step S300, the following steps are further included: Step S400: Detect the compressive strength and metallurgical properties of the vanadium-titanium pellets. The standard for the vanadium-titanium pellets to be qualified products is that the proportion of vanadium-titanium pellets with a particle size of 10mm-16mm accounts for greater than or equal to 80% of the total vanadium-titanium pellets obtained, the compressive strength of the vanadium-titanium pellets is greater than or equal to 2200N / ball, and the reduction expansion rate of the vanadium-titanium pellets is less than or equal to 15%. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0017] Figure 1 A flow chart of a process for preparing vanadium-titanium pellets provided in an embodiment of the present invention; Figure 2 The mineral phase diagram (a) of the vanadium-titanium pellets prepared by the original method and the mineral phase diagram (b) of the preparation method provided in this embodiment. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0019] It should be noted that when an element is referred to as being "disposed on" another element, it may be directly on the other element or indirectly on the other element. It should be understood that the orientation or positional relationship indicated by the terms "length", "width", "upper", "lower", "front", "back", "top", "bottom", "inside", "outside", etc. is based on the orientation or positional relationship shown in the accompanying drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention. The terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "several" is two or more, unless otherwise clearly and specifically defined.

[0020] Please also read Figure 1 to Figure 2 The present invention provides a vanadium-titanium pellet binder, a vanadium-titanium pellet ore and a method for preparing the vanadium-titanium pellet ore. The vanadium-titanium pellet binder comprises, by mass percentage, 7%-9% of boron tail powder, 19%-22% of nickel ore and 70%-74% of Swedish fine powder; the boron tail powder, nickel ore and Swedish fine powder are uniformly mixed to form a vanadium-titanium pellet binder; Among them, the components of Swedish refined powder include: 60%-70% TFe, 2%-3% SiO2, 0.2%-0.3% CaO, 0.4%-0.5% Al2O3, 0.03%-0.05% TiO2, 7%-8% water and other impurities.

[0021] The components of boron tail powder include by mass percentage: 4%-5% TFe, 18%-22% SiO2, 1.0%-1.3% CaO, 1.4%-1.7% Al2O3, 0.07%-0.1% TiO2, 34%-48% MgO, 35%-42% water and other impurities.

[0022] The components of nickel ore include, by mass percentage: 45%-55% TFe, 2.5%-3.5% SiO2, 0.02%-0.05% CaO, 0.2%-0.6% Al2O3, 0.05%-0.05% TiO2, 5%-10% water and other impurities.

[0023] After the boron tail powder, nickel ore and Swedish fine powder are mixed in proportion, the mass percentage of each component is: 54%-57% TFe, 2.0%-2.9% SiO2, 0.15%-0.30% CaO, 1.6%-2.5% MgO, 1.0%-1.8% Al2O3, 0.02%-0.10% TiO2 and other impurities.

[0024] The vanadium-titanium pellet binder provided in the present embodiment, compared with the prior art, can make full use of solid waste products and reduce the cost of the binder. The vanadium-titanium pellet binder acts on vanadium-titanium pellets to reduce the proportion of original bentonite, so that the original bentonite is reduced by 4-6 kg / t compared with the benchmark sample. By using boron tail powder containing magnesium element, the magnesium content is increased by 0.8% compared with the magnesium content in the benchmark sample, thereby improving the compressive strength of the vanadium-titanium pellets, reducing the expansion rate of the vanadium-titanium pellets, effectively improving the quality of the vanadium-titanium pellets, reducing the preparation cost of the vanadium-titanium pellets, and meeting the blast furnace smelting needs.

[0025] ‌TFe stands for total iron element. In geology and chemical analysis, TFe is the total iron content of a rock or ore sample determined by chemical analysis, expressed as a mass fraction. It is one of the main technical indicators for evaluating the quality of iron ore.

[0026] Nickel ore is a limonite with a high content of crystal water, which makes it easier to control the lower limit of roasting temperature and improve the explosion in the furnace. Swedish fine powder is assimilated at 1341℃, which controls the upper limit of roasting temperature and provides sufficient temperature for mineral crystallization.

[0027] Based on the same inventive concept, the embodiment of the present application also provides a vanadium-titanium pellet ore, including 65%-70% by mass of vanadium-titanium iron powder, 1.5%-2.5% by mass of copper powder, 1.5%-2.5% by mass of dust removal ash, 1.3-1.5% by mass of bentonite and a vanadium-titanium pellet binder, wherein the mass percentage of the vanadium-titanium pellet binder is 20%-26%, and the vanadium-titanium iron powder, copper powder, dust removal ash, bentonite and vanadium-titanium pellet binder are roasted to obtain a pellet ore. The mass percentage of vanadium-titanium iron powder is 69%, the mass percentage of copper powder is 2%, the mass percentage of dust removal ash is 2%, the mass percentage of bentonite is 1.4%, and the mass percentage of vanadium-titanium pellet binder is 24%.

[0028] Compared with the prior art, the vanadium-titanium pellets provided in this embodiment can effectively improve the compressive strength of the vanadium-titanium pellets, reduce the expansion rate of the vanadium-titanium pellets, effectively improve the quality of the vanadium-titanium pellets, reduce the preparation cost of the vanadium-titanium pellets, and meet the needs of blast furnace smelting.

[0029] The copper powder assimilation temperature is high at 1271°C, and its fluidity is very good. The appropriate amount of addition can inhibit excessive melting, thereby controlling the medium temperature section of roasting. In the preparation of the above-mentioned vanadium-titanium pellets, the roasting temperature can be effectively controlled and the formation of the liquid phase can be promoted by reacting the vanadium-titanium pellet binder components, thereby strengthening the pellet consolidation behavior and improving the quality of the pellets, thereby achieving the purpose of improving the quality of the pellets.

[0030] Based on the same inventive concept, the present application also provides a process for preparing vanadium-titanium pellets, comprising the following steps: S100: 7.8-8.5% by weight of boron tail powder, 19-22% by weight of nickel ore, and 70-73.2% by weight of Swedish fine powder are mixed to obtain a vanadium-titanium pellet binder; S200: 20%-26% by weight of vanadium-titanium pellet binder, 65%-70% by weight of vanadium-titanium iron powder, 1.5%-2.5% by weight of copper powder, 1.5%-2.5% by weight of dust removal ash and 1.3%-1.5% by weight of bentonite are mixed evenly to form raw balls; S300: drying, preheating, roasting, homogenizing and cooling the green balls in sequence to obtain vanadium-titanium pellets.

[0031] In step S300, the drying bed temperature of the preheating step is 500℃-600℃, the material temperature of the green balls is greater than 60℃, and the cold air volume of the cooling step is 35000m 3 / h-37000m 3 / h, the combustion chamber temperature of the roasting process is 1000-1100℃, and the combustion chamber pressure of the roasting process is 13000m 3 / h-15000m 3 / h.

[0032] Step S400: Detect the compressive strength and metallurgical properties of the vanadium-titanium pellets. The standard for the vanadium-titanium pellets to be qualified products is that the proportion of vanadium-titanium pellets with a particle size of 10mm-16mm accounts for greater than or equal to 80% of the total vanadium-titanium pellets obtained, the compressive strength of the vanadium-titanium pellets is greater than or equal to 2200N / ball, and the reduction expansion rate of the vanadium-titanium pellets is less than or equal to 15%.

[0033] Embodiment 1: A preparation process for vanadium-titanium pellets comprises the following steps: S100: 8.0% by mass of boron tail powder, 20% by mass of nickel ore and 72% by mass of Swedish refined powder are mixed and prepared to obtain a clay-based vanadium-titanium pellet binder.

[0034] S200: 25% by mass of vanadium-titanium pellet binder, 69% of vanadium-titanium iron powder, 2% of copper powder, 2% of dust removal ash and 1.4% of bentonite are mixed evenly and made into green balls. Green balls with a particle size of 10-16mm account for 80% of the total number of green balls, the moisture content of the green balls is 8.0%, the drop strength is 6 times / ball, and the compressive strength is 20N / ball. 6 times / ball means that the green ball is lifted to a certain height, dropped 6 times, and the green ball breaks, which is the number of drops the green ball has experienced. The compressive strength of the green ball detected by the compression machine is 20N / ball.

[0035] S300: The raw balls are sequentially dried, preheated, roasted and evenly heated. The drying bed temperature is 550°C during the preheating process, and the combustion chamber temperature is 1060°C during the roasting process. The balls are then cooled to obtain vanadium-titanium pellets.

[0036] S400: Testing the compressive strength and metallurgical properties of vanadium-titanium pellets. The compressive strength of the vanadium-titanium pellets tested by the compression machine is 3000N / piece, which is 800N / piece higher than the compressive strength of 2200N / piece of vanadium-titanium pellets prepared by the original process.

[0037] In the above preparation process, the amount of bentonite used in vanadium-titanium pellets can be reduced by 4-6kg / t. By using boron tail powder containing magnesium element, the magnesium content of the vanadium-titanium pellets can be increased by 0.8%, the B2O3 content can be increased by 0.14%, the compressive strength of the vanadium-titanium pellets can be increased by 800N / piece, and the expansion rate can be reduced by 3%. The above preparation method can reduce the raw material cost and achieve the purpose of improving the quality of vanadium-titanium pellets.

[0038] Specifically, in the process of preparing the adhesive, the specific values ​​of the chemical composition of each raw material component are shown in Table 1, the basic properties of each raw material component are shown in Table 2, and in the preparation process of vanadium-titanium pellets, the baking parameters of the baking step are shown in Table 3.

[0039] Table 1 Chemical composition analysis of raw materials (mass percentage / %) Mineral powder name TFe SiO2 TiO2 CaO Al2O3 P Copper powder 54.8 12 0.61 1.59 5.07 0.04 Nickel Ore 51.91 2.73 0.14 0.22 6.7 0.038 Swedish Flour 67.38 2.12 0.13 0.25 0.47 0.014 Table 2 Basic characteristics of iron ore powder with different ore powders

[0040] Table 3 Calcination parameters

[0041] The compressive strength and metallurgical properties of the vanadium-titanium pellets obtained according to the above preparation method are shown in Table 4.

[0042] Table 4

[0043] From Table 4 above, it can be seen that the compressive strength of the vanadium-titanium pellets obtained by the preparation method is increased by 800N, the expansion rate is reduced by 3%, the reduction degree is increased by 1.5%, the powder content is effectively reduced, and the load softening range is greatly shortened. The above preparation method improves the quality of the pellets. At the same time, the amount of bentonite added in the preparation of the vanadium-titanium pellet binder is reduced by 4-6kg / t, which has a good effect of reducing costs and improving quality.

[0044] Please refer to the attached Figure 2 In Figure (a), the prior art has relatively more silicate pores and less hematite (the bright white part in the figure is hematite), which is not conducive to improving the strength of the pellets. Figure 2 In Figure (b), the product prepared by the preparation process of vanadium-titanium pellets has reduced pores and silicates, and more hematite is connected together (the bright white part in the figure is hematite), which effectively improves the compressive strength of the vanadium-titanium pellets.

[0045] The preparation process of the vanadium-titanium pellets can effectively improve the low compressive strength and poor metallurgical properties caused by low iron grade during the preparation process. The addition of boron tailings promotes the formation of liquid phase during roasting, effectively improving the compressive strength of the vanadium-titanium pellets.

[0046] The above-mentioned vanadium-titanium pellet preparation process utilizes low-cost boron tailings, nickel ore and Swedish fine powder to prepare a vanadium-titanium pellet binder, which reduces the amount of bentonite by 4kg / t-6kg / t compared with the original binder. At the same time, by using boron tailings containing magnesium, the magnesium content of the vanadium-titanium pellets is increased by 0.8%, and the B2O3 is increased by 0.14%, thereby increasing the compressive strength of the vanadium-titanium pellets by 800N / piece and reducing the expansion rate by 3%. While improving the quality of low-cost vanadium-titanium pellets, the preparation cost of vanadium-titanium pellets is effectively reduced.

[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A vanadium-titanium pellet binder, characterized in that: The components of the vanadium-titanium pellet binder include, by mass percentage, 7%-9% of boron tail powder, 19%-22% of nickel ore and 70%-74% of Swedish fine powder; the boron tail powder, the nickel ore and the Swedish fine powder are uniformly mixed to form the vanadium-titanium pellet binder; The components of the Swedish fine powder include, by mass percentage, 60%-70% TFe, 2%-3% SiO2, 0.2%-0.3% CaO, 0.4%-0.5% Al2O3, 0.03%-0.05% TiO2, 7%-8% water and other impurities.

2. The vanadium-titanium pellet binder according to claim 1, characterized in that: The components of the boron tail powder include, by mass percentage, 4%-5% TFe, 18%-22% SiO2, 1.0%-1.3% CaO, 1.4%-1.7% Al2O3, 0.07%-0.1% TiO2, 34%-48% MgO, 35%-42% water and other impurities.

3. The vanadium-titanium pellet binder according to claim 1, characterized in that: The components of the nickel ore include, by mass percentage, 45%-55% TFe, 2.5%-3.5% SiO2, 0.02%-0.05% CaO, 0.2%-0.6% Al2O3, 0.05%-0.05% TiO2, 5%-10% water and other impurities.

4. The vanadium-titanium pellet binder according to claim 3, characterized in that: After the boron tail powder, the nickel ore and the Swedish fine powder are mixed in proportion, the mass percentage of each component is: 54%-57% TFe, 2.0%-2.9% SiO2, 0.15%-0.30% CaO, 1.6%-2.5% MgO, 1.0%-1.8% Al2O3, 0.02%-0.10% TiO2 and other impurities.

5. A vanadium-titanium pellet, characterized in that: It comprises 65%-70% by mass of vanadium-titanium iron powder, 1.5%-2.5% by mass of copper powder, 1.5%-2.5% by mass of dust ash, 1.3-1.5% by mass of bentonite and the vanadium-titanium pellet binder according to any one of claims 1-3, wherein the mass percentage of the vanadium-titanium pellet binder is 20%-26%. Pellets are obtained after calcining the vanadium-titanium iron powder, the copper powder, the dust ash, the bentonite and the vanadium-titanium pellet binder.

6. The vanadium-titanium pellet according to claim 5, characterized in that: The mass percentage of the vanadium-titanium iron powder is 69%, the mass percentage of the copper powder is 2%, the mass percentage of the dust ash is 2%, the mass percentage of the bentonite is 1.4%, and the mass percentage of the vanadium-titanium pellet binder is 24%.

7. A method for preparing the vanadium-titanium pellets according to claim 5 or 6, characterized in that: The following steps are involved: S100: 7.8-8.5% by weight of boron tail powder, 19-22% by weight of nickel ore, and 70-73.2% by weight of Swedish fine powder are mixed to obtain a vanadium-titanium pellet binder; S200: 20%-26% by weight of the vanadium-titanium pellet binder, 65%-70% by weight of vanadium-titanium iron powder, 1.5%-2.5% by weight of copper powder, 1.5%-2.5% by weight of dust removal ash, and 1.3%-1.5% by weight of bentonite are mixed evenly to form raw balls; S300: drying, preheating, roasting, homogenizing and cooling the green balls in sequence to obtain vanadium-titanium pellets.

8. The method for preparing vanadium-titanium pellets according to claim 7, characterized in that: In step S300, the drying bed temperature of the preheating step is 500°C-600°C, the material temperature of the green balls is greater than 60°C, and the cold air volume of the cooling step is 35000m 3 / h-37000m 3 / h.

9. The method for preparing vanadium-titanium pellets according to claim 7, characterized in that: In step S300, the combustion chamber temperature of the roasting process is 1000-1100°C, and the combustion chamber pressure of the roasting process is 13000m 3 / h-15000m 3 / h.

10. The method for preparing vanadium-titanium pellets according to claim 7, characterized in that: After step S300, the following steps are also included: Step S400: Detecting the compressive strength and metallurgical properties of the vanadium-titanium pellets. The standard for the vanadium-titanium pellets to be qualified products is that the proportion of the vanadium-titanium pellets with a particle size of 10mm-16mm in the total vanadium-titanium pellets obtained is greater than or equal to 80%, the compressive strength of the vanadium-titanium pellets is greater than or equal to 2200N / ball, and the reduction expansion rate of the vanadium-titanium pellets is less than or equal to 15%.